PENGARUH CELEBRITY ENDORSEMENT DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN BRAND EIGER: Studi pada Konsumen Eiger di Wilayah Solo Raya melalui Media Sosial Instagram - Dikma Nanda Mustika Jati; Titin Hargyatni (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to investigate how celebrity endorsements and brand perception influence consumer purchasing choices for Eiger brand products. Quantitative methods and a questionnaire survey were used to collect a sample of 100 consumers from the Solo Raya metropolitan area. After testing for validity, reliability, and traditional assumptions, the data were analyzed using multiple linear regression. The results indicate that celebrity endorsements and brand image have a strong, positive, and simultaneous impact on purchasing decisions. The coefficient of determination, at 89.4%, explains the variance in purchasing decisions. This study provides a useful complement to the Eiger brand's digital marketing plan by prioritizing trusted endorsers and enhancing brand reputation.  Keywords: Celebrity Endorsement, Brand Image, Purchase Decision, Eiger Bran